Lack of financial literacy exacerbates SMEs’ appalling state in Gweru city. - MABHANDA, WILSON (IJRDO - Journal of Business Management, 2015)
Unless policy makers are taken to task the spirit of SMEs in Zimbabwe shall remaindampened for the unforeseeable future. Studies conducted confirmed SME owners ignorantpertaining to further challenges experienced in the business due to lack of financial literacy.The purpose of this study was to explore the impact of financial illiteracy to SMEs in spite ofvarious interventions to promote growth of SMEs. All the participants of this study werepurposefully selected in line with qualitative research approach used in data analysis. Theresearcher employed a qualitative research approach where document analysis, focus groupdiscussions, open-ended questionnaires and face to face interviews were used. The studyrevealed that several factors that include lack of financial education contributed further topoor management skills, poor budgeting skills, lack of business information, poor decisionmaking and lack of non business behaviour. The study revealed a considerable low level offinancial literacy among entrepreneurs and this has far reaching consequences to themanagement of their ventures. Such factors worsened the state of SMEs in Zimbabwe. Thestudy therefore recommends that the government, stakeholders, banks, financial supportinstitutions and individuals conduct financial literacy programmes to revive and strengthenthe viability of SMEs.